treatment of pityiasis versicolor with two weekly dose of systemic fluconazole - Al-Wattar, wifaq M.; Al-mussawy, khalida M.; Al-waiz, Mukarum (Journal of the Faculty of Medicine Baghdad, 2005)
Background: